Exploring lectin–glycan interactions to combat COVID-19: Lessons acquired from other enveloped viruses. (21st October 2020) - Nascimento da Silva, Luís Cláudio; Mendonça, Juliana Silva Pereira; de Oliveira, Weslley Felix; Batista, Karla Lílian Rodrigues; Zagmignan, Adrielle; Viana, Isabelle Freire Tabosa; dos Santos Correia, Maria Tereza
Abstract: The emergence of a new human coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has imposed great pressure on the health system worldwide. The presence of glycoproteins on the viral envelope opens a wide range of possibilities for the application of lectins to address some urgent problems involved in this pandemic. In this work, we discuss the potential contributions of lectins from nonmammalian sources in the development of several fields associated with viral infections, most notably COVID-19. We review the literature on the use of nonmammalian lectins as a therapeutic approach against members of the Coronaviridae family, including recent advances in strategies of protein engineering to improve their efficacy. The applications of lectins as adjuvants for antiviral vaccines are also discussed. Finally, we present some emerging strategies employing lectins for the development of biosensors, microarrays, immunoassays and tools for purification of viruses from whole blood. Altogether, the data compiled in this review highlight the importance of structural studies aiming to improve our knowledge about the basis of glycan recognition by lectins and its repercussions in several fields, providing potential solutions for complex aspects that are emerging from different health challenges.